Intelligent Router for LLM Workloads: Improving Performance Through Workload-Aware Scheduling - Parayil, A.; Mallick, Ankur; Choukse, Esha; Qin, Xiaoting; Zhang, Jue; Goiri, Íñigo; Wang, Rujia; Bansal, Chetan; Ruehle, Victor; Rajmohan, Saravan; Jain, Kunal; Kulkarni, Anoop; et al. (ArXiv, 2024)
Large Language Model (LLM) workloads have distinct prefill and decode phases with different compute and memory requirements which should ideally be accounted for when scheduling input queries across different LLM instances in a cluster. However existing scheduling algorithms treat LLM workloads as monolithic jobs without considering the distinct characteristics of the two phases in each workload. This leads to sub-optimal scheduling and increased response latency. In this work, we propose a heuristic-guided reinforcement learning-based intelligent router for data-driven and workload-aware scheduling. Our router leverages a trainable response-length predictor, and a novel formulation for estimating the impact of mixing different workloads to schedule queries across LLM instances and achieve over 11% lower end-to-end latency than existing approaches.